Quelques mastodontes miocènes du Portugal - Antunes, M. Telles (2008)
From a paleontological point of view previous determinations for some specimens as Tetralophodon longirostris can be confirmed from Azambujeira (upper level), Valverde and Vale de Matança. A so far undescribed and rare D3 (from Azambujeira, middle level) has been studied. For the first time in Portugal a Gomphotherium angustidens transitional to «Tetralophodon» grandincisivus is reported (from Portas do Sol). Teeth from Lisbon formerly reported (in part) to T. longirostris are now ascribed to G. angustidens. The presence of T. longirostris at Vale de Matança excludes a Pliocene age for Marateca Formation. This and some other evidence clearly points out towards an early Vallesian age. G. angustidens transitional to T. grandincisivus found at Portas do Sol is enough to ascribe this locality to the latest Middle Miocene or earliest Upper Miocene. Therefore it is possible to correlate overlying Santarém limestones to the Vallesian Cartaxo and Almoster ones which are better dated.